2019
DOI: 10.3390/met10010027
|View full text |Cite
|
Sign up to set email alerts
|

On the Superplastic Deformation in Vanadium-Alloyed High-Nitrogen Steel

Abstract: The experimental evidence for the realization of a superplastic behavior with 900% elongation in V-alloyed high-nitrogen austenitic Fe-19Cr-22Mn-1.5V-0.3C-0.6N steel was proposed. Using thermomechanical processing, a misoriented grain/subgrain austenitic microstructure with a high density of deformation-assisted defects and precipitates was developed in the steel. During high-temperature tensile deformation in a temperature interval from 850 to 1000 • C and strain-rate range from 4 × 10 −4 s −1 to 6 × 10 −3 s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…The probe has a needle spacing of 635 µm, and a current of 80 mA was imposed between the external needles. Typically, layers comprise skeletal-type ferrite in the non-remelted area and lathy-ferrite in the remelted area between layers [23,39], which is explained by the higher cooling rates in the remelted zone, since it is the first portion of volume to solidify [40].…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…The probe has a needle spacing of 635 µm, and a current of 80 mA was imposed between the external needles. Typically, layers comprise skeletal-type ferrite in the non-remelted area and lathy-ferrite in the remelted area between layers [23,39], which is explained by the higher cooling rates in the remelted zone, since it is the first portion of volume to solidify [40].…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…Due to the fact that the metal of sample № 1 is at temperatures higher than the metal of sample № 2, then the process of diffusion of δ-ferrite into austenite takes place in it. Similar changes in the phase composition were established in [20], where the authors subjected the samples obtained by electron-beam surfacing from AISI 304 steel, followed by heat treatment followed by quenching in water.…”
Section: Solid State Phenomena Vol 328mentioning
confidence: 54%
“…9b). Results of mechanical tests for MTMT specimens show that in temperature interval from 850 to 1000 °C and for strain rate interval from 4.2×10 -4 to 6.3×10 -3 s -1 value of strain rate sensitivity coefficient m varies from 0.4 to 0.49 [22]. Microstructural analysis showed that proposed multistage thermo-mechanical treatment assists to refinement and redistribution of disperse particles of carbonitrides of vanadium and chromium and produces the deformation microstructure in austenite.…”
mentioning
confidence: 98%
“…7b) that MTMT procedure does not allow to produce well-developed ultrafine-grained structure. Instead, a highly defective microstructure with high density of deformation-assisted defects was produced [22].…”
mentioning
confidence: 99%